2006
DOI: 10.4049/jimmunol.176.3.1411
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Form of T Cell Ig Mucin 3 Is an Inhibitory Molecule in T Cell-Mediated Immune Response

Abstract: T cell Ig mucin 3 (Tim-3) has been found to play an important role in Th1-mediated auto- and alloimmune responses, but the function of soluble form of Tim-3 (sTim-3) remains to be elucidated. In this study, we report the inhibitory effect of sTim-3 on T cell-mediated immune response. In this study, sTim-3 mRNA was found, among different tissues and organs, only in splenic cells, and the activation of splenocytes resulted in up-regulated production of both sTim-3 mRNA and protein. We constructed a eukaryotic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 36 publications
2
92
0
Order By: Relevance
“…We previously showed that Tim-3 may act as a signal molecule to promote tumor progression (18). Here, we further provide evidence that Tim-3 expression in endothelial cells in tumor and lung could be induced by the TLR4 ligand.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We previously showed that Tim-3 may act as a signal molecule to promote tumor progression (18). Here, we further provide evidence that Tim-3 expression in endothelial cells in tumor and lung could be induced by the TLR4 ligand.…”
Section: Discussionsupporting
confidence: 53%
“…Eukaryotic expression vector pTim-3 carrying the cDNA encoding full-length mouse Tim-3 was preserved in the laboratory (18). CHO cells were transfected with pTim-3 or pcDNA3.1 with FuGene 6 transfection reagent (Roche, Indianapolis, IN) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The administration of galectin-9 results in a selective reduction of IFN-␥ producing cells and suppression of Th1-mediated autoimmune encephalomyelitis in vivo (13). Soluble form of Tim-3 inhibits Agspecific T cell responses in vitro and reduced antitumor immunity in vivo by inhibiting effector Th1 responses (14). Overall, these data suggest that the Tim-3-Tim-3L pathway may contribute to the attenuation of Th1-mediated responses.…”
Section: Cd25mentioning
confidence: 64%
“…Plasmids were prepared and analyzed as described previously (27). Mice received the injection of plasmid DNA (in 100 ml saline) into the muscle tissue (i.m.…”
Section: In Vivo Gene Transfectionmentioning
confidence: 99%